Ethylene Oliver interviewed by Cynthia Holden in the Australia 1938 oral history project - Oliver, Ethylene, 1908-; Holden, Cynthia; Australia 1788-1988: A Bicentennial History; Australia 1938 Oral History Project (1982)
Oliver speaks of her family background; family lifestyle; the Depression; school and childhood memories; local community of Maryborough; sexism at school; training to be a nurse; experiences nursing; family home; brother's apprenticeship; recreation; religion.
Recorded by the Australia 1938 Oral History Project as research for the book Australians 1938 from the series Australians, a historical library.
Also available online
Timed summary available.
Keywords: Oliver, Ethylene, -- 1908- -- Interviews; Nurses -- Queensland -- Biography; Maryborough (Qld.) -- Social conditions -- 1901-1945.; Maryborough (Qld.) -- Social life and customs -- 1901-1945.